Control of Non-Communicable Diseases in the Indonesian Regulations of Health - Rastiti, Ni Putu; Dharmawan, Ni Ketut Supasti; Astuti, Ika Widi; Winata, I Gde Sastra (Babali Nursing Research, 2025)
Introduction: Non-communicable diseases are chronic diseases that are the most common causes of death worldwide, including in Indonesia. The increase in the prevalence of NCDs occurs year after year and becomes a problem for national health and budget. This challenge is why the enactment of Law Number 17 of 2023 on Health was subsequently followed by the implementation of Government Regulation Number 28 of 2024 on the Implementation Regulations of Law Number 17 of 2023 on Health. This research aims to understand the prevention of non-communicable diseases outlined in this regulation. Method: The research design used a descriptive-analytical approach with a normative-juridical approach. Searching for constitutional norms was used to gather legal resources. Since the analysis was about a legal event or state, a descriptive technique was employed to present it. The case method for the research problem was used. Results: Health promotion, early detection, limiting sugar, salt, and fat intake, controlling tobacco products, physical activity, immunization, and health services are all part of the NCD control strategy, according to Article 192 of Government Regulation Number 28 of 2024 concerning the Implementation Regulation of Law No. 17 of 2023 concerning Health. Conclusion: The prevention of NCDs requires holistic and comprehensive actions,, starting with the formation of government regulations. The government is the policy executor authorized by law to implement public policies to achieve the health administration goals in Indonesia.